Variación de la densidad relativa de la madera de Pinus greggii Engelm. del norte de México - López Locia, Miguel; Valencia Manzo, Salvador (Instituto de Ecología, A.C., 2016)
The objective of this study was to know the wood density variability between and within populations of Pinus greggii Engelm. from northern Mexico. Wood samples were obtained at the diameter breast height (DBH; 1.30 m) of five to eleven trees from twelve populations. Each sample was sectioned into juvenile, transition, and mature wood. Specific gravity had a value of 0.47 that was considered as moderately heavy wood. Wood density differed between populations and between trees within populations. Out of total wood density variability, thirteen percent was attributed to differences between populations and twenty four percent was due to differences between trees within populations. It was found that wood density was positively correlated (r = 0.36) with total tree height, with the height at the base of the crown (r = 0.23), and with tree age (r = 0.30). These results indicated that wood density can be used for selection of populations and individuals in a tree genetic improvement program.